Local Smooth Solution and Non-Relativistic Limit of Radiation Hydrodynamics Equations. (1st August 2010) - Yang Yang, Jianwei Jianwei; Wang Wang, Shu Shu; Li Li, Yong Yong
Abstract : We investigate a multidimensional nonisentropic radiation hydrodynamics model. We study the local existence and the convergence of the nonisentropic radiation hydrodynamics equations via the non-relativistic limit. The local existence of smooth solutions to both systems is obtained. For well-prepared initial data, the convergence of the limit is rigorously justified by an analysis of asymptotic expansion, an energy method, and an iterative scheme. We also establish uniform a priori estimates with respect to ϵ .